P1.21 Comparison of shipped versus freshly frozen self-collected vaginal samples for microbiota assessment. (8th July 2017) - Jb, Holm; Gajer, P; Jb, Holm; Cr, Robinson; Jones, D; Chatterjee, A; Humphrys, M; Lj, Forney; Ravel, J; Kg, Ghanem
Abstract : Introduction: Studies have confirmed that self-collected and clinician-collected mid-vaginal swabs sample the same microbial diversity. Self-collected samples shipped through the mail for PCR-based STI testing has also been validated. We sought to determine if the microbiota of shipped vaginal samples are concordant with freshly frozen samples. Methods: In January-February 2016, 20 women self-collected six mid-vaginal swabs which were then stored in two different nucleic acid preservatives (3 E-swabs in 2 ml of modified C2 (MO BIO) and 3 in 2 ml of Amies/RNALater). Modified C2 was selected for ease of use in laboratory processing and DNA extraction. For each set of 3 swabs, 2 were immediately frozen (−80°C) and one was sent at room temperature to the University of Idaho in a FedEx "Clinical Pak" which was then return shipped to Baltimore. Meta-taxonomic analysis was performed by sequencing the V3-V4 regions of the 16S rRNA gene. Hierarchical clustering of vaginal microbiota was used to assign community state types (CST) to each sample. Bayesian hierarchical models were applied to perform within-women comparisons of shipped and freshly frozen samples. Results: Average duration of transit for the shipped samples was 8 days (SD: 1.60, range: 6–11). Paired comparison of CSTs between a woman's shipped and freshly frozen samples as well as between C2 and Amies/RNALater revealed no differences (100% concordance, kappa: 1.0 for both). After correction for multiple testing, no significant differences between phylotype relative and absolute abundances were detected in C2 or Amies/RNALater groups. Similarly, there were no statistically significant differences between total bacterial loads of shipped versus freshly frozen samples in C2 (p-value: 0.47) or Amies/RNALater (p-value: 0.21) samples. Conclusion: There were no differences in vaginal microbiota composition and structure between a woman's shipped and freshly frozen vaginal samples stored in Amies/RNAlater or C2. These data enable future studies to allow participants to self-collect and mail vaginal microbiota specimens.